A new blockchain investment and energy certificate platform - Han, Chung Seok; Lotfi Ghahroud, Majid; Park, Min Jae; Ghassemi Nejad, Jalil (Cogent Engineering, 2023)
This article proposes a new decentralized asset investment and energy certificate platform: BIC (Blockchain Investment Certificate) which has a Korean patent for its new solution. The platform combines features of decentralized exchanges (DEX), crowdfunding, token economies, and insurance to provide a secure and efficient marketplace for buying and selling energy assets, including renewable energy certificates such as carbon credits. Decarbonization of energy systems has been a recent trend after 2020 where large-scale renewable energy sources (RES) are integrated into the power industry. The new business model and platform in this article offer unique solutions for investors, small and medium-sized enterprises (SMEs), and the overall economy. With its decentralized structure and innovative features, the platform has the potential to accelerate the transition to a low-carbon economy and promote sustainable investment practices. In addition, this platform provides a simple way to offset carbon footprints and support clean energy initiatives, contributing to the fight against climate change. Also, this platform not only supports the renewable energy market, encouraging the generation of renewable electricity on a larger scale but enables businesses to use renewable electricity without investing in costly facilities like solar panels, making renewable energy more accessible. Furthermore, this novel energy certificate platform facilitates the choice of exactly where to buy renewable energy, whether locally or from different regions in different countries, offering flexibility and increasing renewable energy adoption.
Keywords: asset investment trading; decentralized finance; energy trading